A educação em Montaigne : uma perspectiva da diversidade na exercitação do julgamento - Reis, José Antônio dos (2021)
The research aims to approach Montaigne's conception of the “new way” of teaching, exposed in the chapters “Do Pedantismo” and “Da Educação das Crianças” of the Essays, and to propose, from this conception, the derivation of a formation open to dialogue with the diversity of customs and worldviews of the world, for this purpose the chapter “Dos cannibals” is exemplified. In the first two chapters mentioned, the "new way" is opposed to the results of empty and pedantic scholarship. Added to the “new way” is the relevant role of skepticism contributions to denounce and overcome dogmatisms. From this follows the filing, proposed as the center of formation, which has experience and ancient moral philosophy as the subject of its investigation. Drawing on a broad perspective of educational material and its peculiar pedagogical treatment, the pedagogical “new way” can also recognize and promote dialogue with other worldviews, derived from the diversity of ways of life and ways of interpreting the world, such as you can see it in “Dos canibais”. The formative framework proposed by Montaigne aims, in the end, at forming the character of a “sufficient man”, a “man of the world”.